Computational screening for new neuroprotective ingredients against Alzheimer's disease from bilberry by cheminformatics approaches - Xiao, Ran; Liang, Rui; Cai, Yun-hui; Dong, Jie; Zhang, Lin (Frontiers in Nutrition, 2022)
Bioactive ingredients from natural products have always been an important resource for the discovery of drugs for Alzheimer's disease (AD). Senile plaques which formed with amyloid-beta (Aβ) peptides and excess metal ions are found in AD brains and have been suggested to play an important role in AD pathogenesis. Here, we attempted to design an effective and smart screening method based on cheminformatics approaches to find new ingredients against AD from Vaccinium myrtillus (bilberry), and verified the bioactivity of expected ingredients through experiments. This method integrated advanced artificial intelligence models and target prediction methods, to realize the stepwise analysis and filtering of all ingredients. Finally, we obtained the expected new compound Malvidin-3-O-galactoside (Ma-3-gal-Cl). The in vitro experiments showed that Ma-3-gal-Cl could reduce the OH· generation and intracellular ROS from the Aβ/Cu2+/AA mixture, and maintain the mitochondrial membrane potential of SH-SY5Y cells. Molecular docking and western blot results indicated that Ma-3-gal-Cl could reduce the amount of activated caspase-3 via binding with unactivated caspase-3 and reduce the expression of phosphorylated p38 via binding with mitogen-activated protein kinase kinases-6 (MKK6). Moreover, Ma-3-gal-Cl could inhibit the Aβ aggregation via binding with Aβ monomer and fibers. Thus Ma-3-gal-Cl showed significant effects on protecting SH-SY5Y cells from Aβ/Cu2+/AA induced damage via antioxidation effect and inhibition effect to the Aβ aggregation.